DEMOCRATIC CONFLICT AND CONSENSUS:AN ANALYTICAL STUDY OF GENERAL PERVEZ MUSHARRAF ERA 1999-2008 - Soomro, Siraj Ahmed; Sahito, Dr. Imdad Hussain; Khuhro, Dr. Amir Ahmed (The journal of contemporary issues in business and government, 2021)
This study finds the conflicting political issues during General Pervez Musharraf's (GPM) era and examines how he dealt with political conflicts and developed political consensus among the political elites. Variables of this study/survey are General Pervez Musharraf, Conflict, Consensus, and Political Elites. A questionnaire was developed, which distributed 500 University faculty members of Pakistan. Out of 500 received respondents were 252, which is 50.4%. Research hypothesis tested on Statical Package for the Social Sciences (SPSS). The outcomes associated with General Pervez Musharraf's consensus policy for political elites. A significant contribution of political elites develop consensus and eradicate conflict on Lal Masjid conflict, Kala Bagh Damconflict, declaration of emergency. From both a theoretical and a concrete viewpoint of General Pervez Musharraf's political past has important implications on the politics of Pakistan. This research adds to the body of information for future historians by incorporating sound scholarly literature. The results of this study can also be helpful for academicians, scholars of social sciences. There have been studies carried out to determine the influence of military governance on elite politics and how it affects General Pervez Musharraf's political consensus.